(untitled) (Revista del Instituto de Investigación Musicológica "Carlos Vega", 2025)
Every editing process is a process of selection, of decision-making. Editing music, especially of ancient documents, involves not only a deep understanding of the sources and their context, but also the inexorable reality of clearly supporting the decisions that the editor makes based on that knowledge. In this case, we will share some of the decisions we made when undertaking the transcription and editing of a significant portion of Juan Gutiérrez de Padilla’s work, his Christmas carols.